Anak Homeschooling: Studi Pada Keluarga Pelaku Homeschooling - Khairi, Alfin Miftahul; Rahayu, Dewi Sri (SHAHIH: Journal of Islamicate Multidisciplinary, 2018)
Homeschooling can be an alternative to education in addition to existing formal education. Because of children learn everything, they must be controled and supervised by parents. Family must have a strong commitment in carrying out them. This research is a phenomenological approach focused on discussing the phenomenon of homeschooling. The purpose of this study was to find out the learning methods used in the learning process and the results obtained from the learning process through homeschooling. Data collection uses the method of observation, interviews and documentation. Data analysis used descriptive qualitative method and data validity was done by triangulation. The results are in the behavioristic approach, children love the learning process because it is fun and can be anywhere. Cognitively, children can adjust their ability to learn. In humanistic children they are aware of the conditions and environment around them. 2) Learning Outcomes show children's progress in cognitive, affective and psychomotor.